VD_FINDINFO HC / 2013 / 730 vom 21. Oktober 2013 - VD Tribunal cantonal (2013)
DIVORCE, OBLIGATION D'ENTRETIEN, PERSONNE DIVORCÉE | 125 al. 1 CC, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH)